Association between cardiometabolic index and postmenopausal stress urinary incontinence: a cross-sectional study from NHANES 2013 to 2018 - Ting Yin; Yue He; Huifang Cong (Lipids in Health and Disease)
Abstract Background Stress urinary incontinence (SUI) is a common condition affecting the genitourinary system in postmenopausal women. Obesity and dyslipidemia are recognized as significant factors that contribute to the onset of SUI. The cardiometabolic index (CMI), a reliable indicator of health risks associated with obesity, is crucial in assessing these risks. This study aims to investigate the relationship between CMI and the occurrence of SUI in postmenopausal women across the United States. Methods This cross-sectional study employed data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2018, concentrating on postmenopausal women aged 40 years and above in the United States. Multiple regression models were utilized to evaluate the association between CMI and postmenopausal SUI, while controlling for pertinent confounding variables. Smooth curve fitting (SCF) techniques were utilized to evaluate the correlation between postmenopausal SUI incidence and CMI. To enhance the robustness of the findings, analyses of subgroups and assessments of interactions were performed. Results 542 postmenopausal women participated in the study, with 237 of them indicating the presence of symptoms associated with stress urinary incontinence. The findings from the multiple regression analysis consistently demonstrated a positive correlation between CMI and SUI in all adjusted models. In particular, a one-unit increase in CMI correlated with a 63% greater probability of encountering postmenopausal SUI in fully adjusted models (OR = 1.63, 95% CI: 1.07–2.48). Additionally, a direct correlation was noted between CMI levels and the occurrence of SUI within this population. Subgroup analysis by the number of vaginal deliveries showed a significant interaction (P for interaction = 0.0471). Conclusions The findings emphasize the importance of managing CMI levels to identify postmenopausal women at increased risk for SUI. This study confirms the strong predictive value of CMI for SUI in this population.